2019
DOI: 10.3847/1538-4357/aafe0c
|View full text |Cite
|
Sign up to set email alerts
|

The First Tidal Disruption Flare in ZTF: From Photometric Selection to Multi-wavelength Characterization

Abstract: We present Zwicky Transient Facility (ZTF) observations of the tidal disruption flare AT2018zr/PS18kh reported by Holoien et al. and detected during ZTF commissioning. The ZTF light curve of the tidal disruption event (TDE) samples the rise-to-peak exceptionally well, with 50 days of g-and r-band detections before the time of maximum light. We also present our multi-wavelength 2 van Velzen et al.follow-up observations, including the detection of a thermal (kT ≈ 100 eV) X-ray source that is two orders of magnit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 102 publications
7
81
0
Order By: Relevance
“…We compare the optical and UV spectra of ASASSN-18jd to well-studied TDEs, other extragalactic transients, and objects with similar spectra in Figures 15 and 16. In Figure 15, we compare two early-time optical spectra of ASASSN-18jd to known TDEs (Holoien et al 2014(Holoien et al , 2016aHung et al 2017;Blagorodnova et al 2019;Hung et al 2019), as well as the composite quasar spectrum from Vanden Berk et al (2001), an early-time spectrum of the TDE candidate PS16dtm (Blanchard et al 2017), an early-time spectrum of the rapid turn-on event ZTF18aajupnt/AT 2018dyk (Frederick et al 2019), and the spectrum of a WR star with strong He ii and N iii-v features (Yaron & Gal-Yam 2012). In Figure 16, we compare a UV spectrum of ASASSN-18jd to TDEs with published UV spectra (Cenko et al 2016;Brown et al 2018;Blagorodnova et al 2019;Hung et al 2019), the composite quasar spectrum from Vanden Berk et al (2001), and an "N-rich" quasar spectrum (Batra & Baldwin 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We compare the optical and UV spectra of ASASSN-18jd to well-studied TDEs, other extragalactic transients, and objects with similar spectra in Figures 15 and 16. In Figure 15, we compare two early-time optical spectra of ASASSN-18jd to known TDEs (Holoien et al 2014(Holoien et al , 2016aHung et al 2017;Blagorodnova et al 2019;Hung et al 2019), as well as the composite quasar spectrum from Vanden Berk et al (2001), an early-time spectrum of the TDE candidate PS16dtm (Blanchard et al 2017), an early-time spectrum of the rapid turn-on event ZTF18aajupnt/AT 2018dyk (Frederick et al 2019), and the spectrum of a WR star with strong He ii and N iii-v features (Yaron & Gal-Yam 2012). In Figure 16, we compare a UV spectrum of ASASSN-18jd to TDEs with published UV spectra (Cenko et al 2016;Brown et al 2018;Blagorodnova et al 2019;Hung et al 2019), the composite quasar spectrum from Vanden Berk et al (2001), and an "N-rich" quasar spectrum (Batra & Baldwin 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some recently discovered TDEs have shown deviations from monotonic fading: ASASSN-18ul showed a light curve plateau ∼40 d after peak brightness (Wevers et al 2019b) and ASASSN-19bt showed a short flare before reaching peak brightness (Holoien et al 2019b). In a more extreme example, PS18kh showed a UV re-brightening ∼50 d after peak (Holoien et al 2019a) and then, after a seasonal gap due Sun constraints, appeared to return to near-peak luminosity (van Velzen et al 2019a). However, these deviations from monotonic fading were still "smooth", with little short-timescale variation, which is qualitatively different from the bumpiness in the light curve of ASASSN-18jd.…”
Section: Asassn-18jd As a Tdementioning
confidence: 99%
See 3 more Smart Citations